The Frontier of Biosensors: The Polymerase Chain Reaction‐Free Approach for Point‐of‐Care Devices - Sabrina Conoci (ChemistryEurope)
The nucleic acids (NA) analysis is spread out by the invention of polymerase chain reaction (PCR). Even though the method has proven to be a disruptively innovation in the medical field, by creating a new of sector of molecular diagnostics, it however remains the prerogative of analysis of laboratories, due to its complexity and cost. To further make progresses in this sector, the development of point‐of‐care (POC) genetic testing technologies is crucial by offering the advantages to be fast, sensitive and specific, low cost, and, above all, able to be used onsite by nonspecialized people. In this context, the PCR‐free approaches are very relevant since they do not need amplification processes and, therefore, they simplify significantly the experimental set up aimed to detect the NA. In this perspective, an overview of most innovative approaches for genetic point care technologies rapid test is presented and discussed particularly appealing to be integrated in portable and easy‐to‐use POC devices.